Preparation method of high-energy-density lithium ion battery based on silicon-based composite negative electrode

The silicon-based composite material prepared by porous silicon, graphene and polyvinylpyrrolidone ball milling combines organic metal frame and pyrrole coating to solve the problem of structural instability of silicon negative electrodes at high temperatures, improves the energy density and cycle life of lithium-ion batteries, and is used in the field of lithium-ion batteries.

CN120497462APending Publication Date: 2025-08-15SHANDONG AOYU POWER SUPPLY

Patent Information

Application Number
CN202510995679.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-18
Publication Date
2025-08-15

AI Technical Summary

Technical Problem

In the prior art, the single-layer material coated silicon anode material is unstable under high temperature conditions, resulting in insufficient energy density and cycle life of lithium-ion batteries.

Method used

The precursor was prepared by ball milling of porous silicon, graphene and polyvinylpyrrolidone. The silicon-based composite material with a porous structure and high electron conductivity was prepared by an organic metal frame and a two-layer pyrrole coated silicon-based composite material, combined with prelithiation and carbonization treatment, and the growth of lithium dendrites was suppressed using a ferrous doped hydrotalcite electrolyte film.

Benefits of technology

It improves the energy density and cycle life of lithium-ion batteries under high temperature conditions, extends the service life, avoids negative electrode powdering failure and electrolyte contact caused by silicon expansion, and achieves excellent electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a preparation method of a high-energy-density lithium ion battery based on a silicon-based composite negative electrode. Porous silicon, graphene, melamine and polyvinylpyrrolidone are subjected to ball milling to prepare a precursor, the precursor is subjected to two-layer coating through an organic metal framework and pyrrole, and finally pre-lithiation and carbonization treatment are performed to prepare the silicon-based composite material, and the porous structure of the porous silicon can relieve volume expansion stress; more defects and reaction point locations are increased by doping the nitrogen element; the double-layer coating of the organic metal framework and pyrrole can increase the adsorption of the silicon composite material to lithium ions and improve the electronic conductivity of the material. The lithium battery prepared by the invention has excellent energy density and cycle life under a high-temperature condition, the growth of lithium dendrites is inhibited by the iron-doped hydrotalcite in the electrolyte film, and the negative electrode pulverization failure caused by silicon expansion is inhibited by double-layer coating of the flexible coating layer formed by polymerization of the organic metal framework of the silicon composite material and pyrrole; and direct contact between silicon and electrolyte is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for preparing a high energy density lithium ion battery based on a silicon-based composite negative electrode. Background Art

[0002] Lithium-ion batteries are mainly composed of five parts: positive electrode, separator, negative electrode, electrolyte, and current collector. The positive electrode and negative electrode have a key impact on the energy density, capacity, and cycle life of lithium-ion batteries. Graphite, as the most widely used negative electrode material, has a low theoretical capacity and can no longer meet the growing demand for high-capacity lithium-ion batteries. Therefore, the development of negative electrode materials with larger capacity is a key direction for the future development of lithium-ion batteries. Silicon-based negative electrodes have the advantages of high theoretical capacity, abundant resource reserves, and environmental friendliness. However, the volume of silicon-based negative electrodes still changes significantly during charge and discharge, resulting in pulverization of silicon-based negative electrode materials, electrical contact failure, and loss of active substances, causing battery failure.

[0003] Chinese invention patent publication number CN117691096B discloses a silicon-based composite anode material for all-solid-state lithium batteries and its preparation method. Silicon nanoparticles are modified with polyvinyl pyrrolidone and dissolved in an In(NO₃)₃·xH₂O solution in N,N'-dimethylformamide. Terephthalic acid is then added to obtain a mixed solution. The mixed solution is heated to react, then centrifuged and the precipitate is collected. The precipitate is washed and dried to obtain a precursor, Si@In-MOF. The Si@In-MOF precursor is then pyrolyzed in air or argon to obtain the composite material, Si@In₂O₃ or Si@In₂O₃ / C.

[0004] Chinese invention patent publication number CN114628652B discloses a long-cycle fast-charging SiO2 graphite composite negative electrode material and its preparation method. The SiO2 graphite composite negative electrode material is prepared by high-temperature kneading of SiO2, graphite, a binder, and a nanoporous elastic alloy. In the present invention, the carbon prepared by high-temperature kneading of the binder is first wrapped with SiO2 and a nano-elastic porous alloy into balls to prepare primary SiO2 particles, and then graphite is wrapped around the outside of the primary SiO2 particles to prepare the SiO2 graphite composite negative electrode material.

[0005] Although the existing technology can improve the expansion and cycle performance of silicon negative electrode materials, there is still a technical problem that the single-layer material-coated silicon negative electrode material is structurally unstable under high temperature conditions. Therefore, further research is needed on silicon-based composite materials, especially the structure and coating method of silicon, in order to improve the thermal stability and coulombic efficiency of silicon-based composite materials. Summary of the Invention

[0006] The purpose of the present invention is to provide a method for preparing a high-energy-density lithium-ion battery based on a silicon-based composite negative electrode, which is used to solve the technical problem in the prior art that the single-layer material-coated silicon negative electrode material is structurally unstable under high temperature conditions.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions: The method for preparing a high energy density lithium ion battery based on a silicon-based composite negative electrode comprises the following steps: S1. Preparing a positive electrode sheet: mixing lithium nickel cobalt manganese oxide, acetylene black, carbon nanotubes and polyvinylidene fluoride, adding the mixture to N,N'-dimethylformamide to prepare a positive electrode slurry, coating the mixture on a current collector, and drying the mixture to prepare a positive electrode sheet; S2. Prepare the negative electrode: mix the silicon-based composite material, polyvinylidene fluoride and acetylene black, add N,N'-dimethylformamide to prepare the negative electrode slurry, apply it on the current collector, and dry it to prepare the silicon-based composite negative electrode; S3. Assemble the battery: Assemble the negative electrode sheet, separator, electrolyte film and positive electrode sheet in an argon atmosphere in order from bottom to top to produce a high energy density lithium-ion battery based on a silicon-based composite negative electrode.

[0008] In the negative electrode plate, the mass ratio of the silicon-based composite material, polyvinylidene fluoride and acetylene black is (75~80): (10~15): (15~20); in the positive electrode plate, the mass ratio of lithium nickel cobalt manganese oxide, acetylene black, carbon nanotubes and polyvinylidene fluoride is (94~96): (1.5~2): (0.2~0.3): (1.5~2); the separator is a polypropylene film.

[0009] The method for preparing the silicon-based composite material comprises the following steps: S11, placing elemental silicon powder and metallic magnesium powder into a ball mill and milling them in an argon atmosphere, heating the mixture to react to obtain a magnesium-silicon alloy, etching the magnesium-silicon alloy in hydrochloric acid and hydrofluoric acid in sequence, washing, and drying the mixture to obtain porous silicon powder; S12, placing porous silicon powder, graphene, melamine and polyvinyl pyrrolidone in a ball mill and milling them to obtain a precursor, adding the precursor and ferric chloride to deionized water, adding dropwise an ethanol solution of fumaric acid, reacting at room temperature, washing with deionized water, drying and calcining to obtain a metal-organic framework-encapsulated silicon material, adding pyrrole and the metal-organic framework-encapsulated silicon material to deionized water for reaction to obtain a composite silicon alloy; S13. Add metallic lithium and biphenyl to tetrahydrofuran for reaction to obtain a pre-lithiation reagent, add the composite silicon alloy to the pre-lithiation reagent for pre-lithiation reaction, then add it to a phosphoric acid solution for reaction to remove lithium, wash with deionized water, dry, and then carbonize at high temperature, and grind to obtain a silicon-based composite material.

[0010] Preferably, the mass ratio of elemental silicon powder and metallic magnesium powder in the S11 is 1:(9~10), and the powder is ball-milled at a speed of 300~500 rpm in an argon atmosphere for 3~4 hours, heated to 600~700°C for reaction for 4~6 hours, etched in 5wt% hydrochloric acid for 4~6 hours, and then etched in 5wt% hydrofluoric acid for 4~6 hours.

[0011] Preferably, the mass ratio of porous silicon powder, graphene, melamine and polyvinyl pyrrolidone in the S12 is 3: (1~1.3): (0.4~0.5): (0.3~0.4), and the ball milling is carried out at a speed of 300~500rpm for 3~4h. The mass ratio of the precursor, ferric chloride and fumaric acid is 1: (2.6~3): (1~1.3). After adding an ethanol solution of fumaric acid dropwise, the mixture is reacted at room temperature for 20~24h, washed with deionized water and dried, and then calcined at 700~800℃ for 4~6h.

[0012] Preferably, the mass ratio of the silicon material encapsulated by the metal organic framework to pyrrole in S12 is 10:1-2, and the silicon material is added to deionized water and reacted at room temperature for 1-2 hours.

[0013] Preferably, the molar ratio of metallic lithium to biphenyl in S13 is (2-2.2):1, metallic lithium and biphenyl are added to tetrahydrofuran and reacted at room temperature for 10-12 hours, the composite silicon alloy is added to the pre-lithiation reagent and pre-lithiation is reacted at room temperature for 10-12 hours, and then added to a 30-40 g / L phosphoric acid solution and reacted at room temperature for 4-6 hours, and carbonized at a high temperature of 800-850 ° C for 2-4 hours.

[0014] The method for preparing the electrolyte film comprises the following steps: S21, adding ferric chloride, aluminum chloride and magnesium chloride to deionized water, adding sodium hydroxide and sodium bicarbonate dropwise to adjust the pH to 9.5-10, heating to crystallize, drying and grinding to obtain iron-doped hydrotalcite; S22. Mix lithium bis(trifluoromethanesulfonyl imide) and lithium dioxalatoborate, add 1-methyl-3-hexylimidazole fluoromethanesulfonyl imide ionic liquid, heat and stir, and vacuum dry to obtain a lithium-containing mixture, mix the lithium-containing mixture and iron-doped hydrotalcite, add poly(vinylidene fluoride-co-hexafluoropropylene) and N,N'-dimethylformamide, stir and dissolve, and then hot press to obtain an electrolyte film.

[0015] Preferably, the molar ratio of ferric chloride, aluminum chloride and magnesium chloride in S21 is (0.1-0.2): (1.3-1.5): (5-6), the molar ratio of sodium hydroxide and sodium bicarbonate is 4:1, and the temperature is raised to 80-90° C. for crystallization for 8-12 hours.

[0016] Preferably, the molar ratio of lithium bis(trifluoromethanesulfonyl imide), lithium bis(oxalatoborate) and 1-methyl-3-hexylimidazole fluoromethanesulfonyl imide ionic liquid in S22 is (0.5-0.6): (0.3-0.4): 4.5, the temperature is raised to 50-60° C. and stirred for 10-12 hours, and the mass ratio of the lithium-containing mixture, hydrotalcite and poly(vinylidene fluoride-co-hexafluoropropylene) is 1:1:(8-10).

[0017] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. The present invention prepares porous silicon by etching a magnesium-silicon alloy with hydrochloric acid, then ball-mills the porous silicon, graphene, melamine, and polyvinyl pyrrolidone to prepare a precursor, reacts ferric chloride and fumaric acid on the surface of the precursor to form an organic metal framework, which is then polymerized and coated with pyrrole, and finally pre-lithiated and carbonized to prepare a silicon-based composite material. The porous structure of the porous silicon can alleviate the volume expansion stress generated by charging and discharging, shorten the lithium ion transmission path, and improve the electrochemical performance of the silicon negative electrode. Melamine is introduced into the precursor, and more lattice defects and reaction sites are added by doping nitrogen, thereby improving the interfacial bonding ability between the organic metal framework and the precursor and the electronic conductivity of the silicon composite material. The rigid framework of the organic metal framework and the flexible coating formed by pyrrole polymerization form a double-layer synergistic coating to further alleviate the volume expansion stress of the silicon material. The organic metal framework has regular pores. Through carbonization, a silicon composite material can be obtained that can increase the adsorption of lithium ions to the silicon composite material, improve the electronic conductivity of the material, and pre-lithiation compensates for the lithium loss during the initial charge and discharge of the silicon negative electrode, thereby extending the service life of the lithium battery.

[0018] 2. The present invention prepares iron-doped hydrotalcite by crystallization reaction of ferric chloride, aluminum chloride and magnesium chloride, and then hot-presses it with lithium bis(trifluoromethanesulfonylimide), lithium bis(oxalatoborate), ionic liquid and poly(vinylidene fluoride-co-hexafluoropropylene) to obtain an electrolyte film. The introduction of iron ions increases the charge density of the layer plate, expands the interlayer spacing, and facilitates the migration of lithium ions. The layered structure can adsorb lithium ions and ionic liquid, increasing the migration path of lithium ions. Lithium bis(trifluoromethanesulfonylimide) and lithium bis(oxalatoborate) are mixed as lithium sources. Lithium bis(trifluoromethanesulfonylimide) can promote the formation of a stable solid electrolyte interface film on the negative electrode surface. Mixing with lithium bis(trifluoromethanesulfonylimide) avoids corrosion of the aluminum current collector and has high conductivity. 1-methyl-3-hexylimidazole fluoromethylsulfonylimide ionic liquid is used as the matrix medium of the electrolyte. It has high-temperature stability, can avoid ionic liquid leakage caused by ionic liquid swelling, and achieves flexible film formation.

[0019] 3. The silicon composite material and electrolyte film prepared by the present invention are used to prepare lithium batteries. The iron-doped hydrotalcite in the electrolyte film can inhibit the growth of lithium dendrites through spatial constraints. The double-layer coating of the metal frame of the silicon composite material and the flexible coating formed by pyrrole polymerization inhibits the pulverization failure of the negative electrode caused by silicon expansion, avoids direct contact between silicon and electrolyte, and enables the lithium battery to have excellent energy density and cycle life under high temperature conditions. DETAILED DESCRIPTION

[0020] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0021] The current collector involved in the present invention is an aluminum foil current collector with an average thickness of 10 μm; the diaphragm is a single-layer polypropylene film with an average thickness of 25 μm, a porosity of 47%, and an average pore size of 0.041 μm.

[0022] Example 1: The method for preparing a high energy density lithium-ion battery based on a silicon-based composite negative electrode of this embodiment comprises the following steps: S1. Preparation of positive electrode sheet: lithium nickel cobalt manganese oxide, acetylene black, carbon nanotubes and polyvinylidene fluoride were mixed in a mass ratio of 96:1.5:0.25:1.5, added to N,N'-dimethylformamide to prepare a positive electrode slurry with a solid content of 75 wt%, coated on a current collector, and dried to obtain a positive electrode sheet with a thickness of 80 μm; S2. Prepare the negative electrode: mix the silicon-based composite material, polyvinylidene fluoride and acetylene black in a mass ratio of 75:10:15, add N,N'-dimethylformamide to prepare a negative electrode slurry with a solid content of 60wt%, apply it on the current collector, and dry it to obtain a silicon-based composite negative electrode sheet with a thickness of 110μm; S3. Assemble the battery: Assemble the negative electrode sheet, separator, electrolyte film and positive electrode sheet in an argon atmosphere in order from bottom to top to produce a high energy density lithium-ion battery based on a silicon-based composite negative electrode.

[0023] The method for preparing the silicon-based composite material of this embodiment comprises the following steps: S11. 2 g of elemental silicon powder and 18 g of metallic magnesium powder were placed in a ball mill, ball-milled at 500 rpm in an argon atmosphere for 4 h, heated to 700° C. and reacted for 6 h to obtain a magnesium-silicon alloy with an average particle size of 10 μm, etched in 5 wt % hydrochloric acid for 6 h, then etched in 5 wt % hydrofluoric acid for 4 h, washed, and dried to obtain porous silicon powder. S12, 0.6 g of porous silicon powder, 0.22 g of graphene, 0.08 g of melamine and 0.06 g of polyvinyl pyrrolidone were placed in a ball mill and ball-milled at a speed of 500 rpm for 4 h to obtain a precursor, 0.5 g of the precursor and 1.3 g of ferric chloride were added to 50 mL of deionized water, 35 mL of an ethanol solution of fumaric acid with a concentration of 15.5 g / L was added dropwise, and the mixture was reacted at room temperature for 24 h. The mixture was washed with deionized water, dried and calcined at 700 ° C for 4 h to obtain a metal-organic framework-encapsulated silicon material, 0.1 g of pyrrole and 0.5 g of the metal-organic framework-encapsulated silicon material were added to 20 mL of deionized water and reacted at room temperature for 2 h to obtain a composite silicon alloy; S13. Add 0.15 g of metallic lithium and 1.5 g of biphenyl to 20 mL of tetrahydrofuran and react at room temperature for 12 hours to obtain a pre-lithiation reagent. Add 0.5 g of a composite silicon alloy to the pre-lithiation reagent and react for 10 to 12 hours. Then add the mixture to a 30 g / L phosphoric acid solution and react at room temperature for 4 hours to remove lithium. Wash with deionized water, dry, and carbonize at 800°C for 4 hours. Grind to obtain a silicon-based composite material.

[0024] The method for preparing the electrolyte film of this embodiment includes the following steps: S21, adding 0.12 g of ferric chloride, 1.65 g of aluminum chloride and 4.62 g of magnesium chloride to 50 mL of deionized water, adding sodium hydroxide and sodium bicarbonate in a molar ratio of 4:1 dropwise to obtain an aqueous solution, adjusting the pH to 10, heating to 80° C. and crystallizing for 8 h, drying and grinding to obtain iron-doped hydrotalcite; S22. Mix 0.24 g of lithium bis(trifluoromethanesulfonyl)imide and 0.12 g of lithium dioxalatoborate, add 2.72 g of 1-methyl-3-hexylimidazole fluoromethanesulfonyl imide ionic liquid, heat to 60°C and stir for 12 h, and vacuum dry to obtain a lithium-containing mixture. Take 0.5 g of the lithium-containing mixture and 0.5 g of iron-doped hydrotalcite and mix them, add 4 g of poly(vinylidene fluoride-co-hexafluoropropylene) and 20 mL of N,N'-dimethylformamide, stir to dissolve, and then hot press to obtain an electrolyte film.

[0025] Example 2: The method for preparing a high energy density lithium-ion battery based on a silicon-based composite negative electrode of this embodiment comprises the following steps: S1. Prepare a positive electrode sheet: lithium nickel cobalt manganese oxide, acetylene black, carbon nanotubes, and polyvinylidene fluoride are mixed in a mass ratio of 94:2:0.2:2, added to N,N'-dimethylformamide to prepare a positive electrode slurry with a solid content of 75 wt%, coated on a current collector, and dried to obtain a positive electrode sheet with a thickness of 100 μm; S2. Prepare the negative electrode: mix the silicon-based composite material, polyvinylidene fluoride and acetylene black in a mass ratio of 75:15:20, add N,N'-dimethylformamide to prepare a negative electrode slurry with a solid content of 60 wt%, apply it on the current collector, and dry it to obtain a silicon-based composite negative electrode sheet with a thickness of 110 μm; S3. Assemble the battery: Assemble the negative electrode sheet, separator, electrolyte film and positive electrode sheet in an argon atmosphere in order from bottom to top to produce a high energy density lithium-ion battery based on a silicon-based composite negative electrode.

[0026] The method for preparing the silicon-based composite material of this embodiment comprises the following steps: S11. 2 g of elemental silicon powder and 20 g of metallic magnesium powder were placed in a ball mill, and ball-milled at 300 rpm in an argon atmosphere for 4 h. The mixture was heated to 600° C. and reacted for 4 h to obtain a magnesium-silicon alloy with an average particle size of 9 μm. The mixture was etched in 5 wt % hydrochloric acid for 5 h, and then etched in 5 wt % hydrofluoric acid for 5 h. The porous silicon powder was washed and dried. S12, 0.6 g of porous silicon powder, 0.2 g of graphene, 0.09 g of melamine and 0.08 g of polyvinyl pyrrolidone were placed in a ball mill and ball-milled at a speed of 500 rpm for 3 h to obtain a precursor, 0.5 g of the precursor and 1.4 g of ferric chloride were added to deionized water, 35 mL of an ethanol solution of fumaric acid with a concentration of 15.5 g / L was added dropwise, and the mixture was reacted at room temperature for 20 h. The mixture was washed with deionized water, dried and calcined at 750 ° C for 4 h to obtain a metal-organic framework-encapsulated silicon material, 0.1 g of pyrrole and 0.6 g of the metal-organic framework-encapsulated silicon material were added to 20 mL of deionized water and reacted at room temperature for 2 h to obtain a composite silicon alloy; S13. Add 0.29 g of metallic lithium and 3.08 g of biphenyl to 20 mL of tetrahydrofuran and react at room temperature for 10 hours to obtain a pre-lithiation reagent. Add 0.6 g of a composite silicon alloy to the pre-lithiation reagent and react for 10 hours. Then add the mixture to a 30 g / L phosphoric acid solution and react at room temperature for 4 hours to remove lithium. Wash with deionized water, dry, and carbonize at 850°C for 2 hours. Grind to obtain a silicon-based composite material.

[0027] The method for preparing the electrolyte film of this embodiment includes the following steps: S21, adding 0.15 g of ferric chloride, 1.72 g of aluminum chloride and 4.84 g of magnesium chloride to 50 mL of deionized water, adding sodium hydroxide and sodium bicarbonate in a molar ratio of 4:1 to obtain an aqueous solution, adjusting the pH to 10, heating to 90° C. and crystallizing for 8 h, drying and grinding to obtain iron-doped hydrotalcite; S22. Mix 0.44 g of lithium bis(trifluoromethanesulfonyl)imide and 0.15 g of lithium dioxalatoborate, add 3.3 g of 1-methyl-3-hexylimidazole fluoromethanesulfonyl imide ionic liquid, heat to 50°C and stir for 10 h, and vacuum dry to obtain a lithium-containing mixture. Mix 0.6 g of the lithium-containing mixture and 0.6 g of iron-doped hydrotalcite, add 6 g of poly(vinylidene fluoride-co-hexafluoropropylene) and 25 mL of N,N'-dimethylformamide, stir to dissolve, and then hot-press to obtain an electrolyte film.

[0028] Example 3: The method for preparing a high energy density lithium-ion battery based on a silicon-based composite negative electrode of this embodiment comprises the following steps: S1. Prepare a positive electrode sheet: lithium nickel cobalt manganese oxide, acetylene black, carbon nanotubes, and polyvinylidene fluoride are mixed in a mass ratio of 96:1.5:0.25:1.5, added to N,N'-dimethylformamide to prepare a positive electrode slurry with a solid content of 75 wt%, coated on a current collector, and dried to obtain a positive electrode sheet with a thickness of 120 μm; S2. Prepare the negative electrode: mix the silicon-based composite material, polyvinylidene fluoride and acetylene black in a mass ratio of 80:10:20, add N,N'-dimethylformamide to prepare a negative electrode slurry with a solid content of 60wt%, apply it on the current collector, and dry it to obtain a silicon-based composite negative electrode sheet with a thickness of 110μm; S3. Assemble the battery: Assemble the negative electrode sheet, separator, electrolyte film and positive electrode sheet in an argon atmosphere in order from bottom to top to produce a high energy density lithium-ion battery based on a silicon-based composite negative electrode.

[0029] The method for preparing the silicon-based composite material of this embodiment comprises the following steps: S11. 2 g of elemental silicon powder and 19 g of metallic magnesium powder were placed in a ball mill, ball-milled at 300 rpm in an argon atmosphere for 4 h, heated to 600° C. and reacted for 4 h to obtain a magnesium-silicon alloy with an average particle size of 8 μm, etched in 5 wt % hydrochloric acid for 4 h, then etched in 5 wt % hydrofluoric acid for 4 h, washed, and dried to obtain porous silicon powder; S12, 3g of porous silicon powder, 1g of graphene, 0.4g of melamine and 0.3g of polyvinyl pyrrolidone were placed in a ball mill and ball-milled at 400rpm for 4h to obtain a precursor, 0.5g of the precursor and 1.5g of ferric chloride were added to deionized water, 36mL of 15g / L ethanol solution of fumaric acid was added dropwise, and the mixture was reacted at room temperature for 22h, washed with deionized water, dried and calcined at 800℃ for 6h to obtain a metal-organic framework-encapsulated silicon material, 0.14g of pyrrole and 0.7g of metal-organic framework-encapsulated silicon material were added to 30mL of deionized water and reacted at room temperature for 1.5h to obtain a composite silicon alloy; S13. Add 0.3 g of metallic lithium and 3.08 g of biphenyl to 30 mL of tetrahydrofuran and react at room temperature for 12 hours to obtain a pre-lithiation reagent. Add 0.7 g of composite silicon alloy to the pre-lithiation reagent and react for 12 hours. Then add it to 40 g / L phosphoric acid solution and react at room temperature for 6 hours to remove lithium. Wash with deionized water, dry it, and carbonize it at 850°C for 3 hours. Grind it to obtain a silicon-based composite material.

[0030] The method for preparing the electrolyte film of this embodiment includes the following steps: S21, adding 0.15 g of ferric chloride, 1.85 g of aluminum chloride and 5.18 g of magnesium chloride to 50 mL of deionized water, adding sodium hydroxide and sodium bicarbonate in a molar ratio of 4:1 to obtain an aqueous solution, adjusting the pH to 10, heating to 90° C. and crystallizing for 12 h, drying and grinding to obtain iron-doped hydrotalcite; S22. Mix 0.33 g of lithium bis(trifluoromethanesulfonyl)imide and 0.15 g of lithium dioxalatoborate, add 2.55 g of 1-methyl-3-hexylimidazole fluoromethanesulfonyl imide ionic liquid, heat to 60°C and stir for 10 h, and vacuum dry to obtain a lithium-containing mixture. Mix 0.5 g of the lithium-containing mixture and 0.5 g of iron-doped hydrotalcite, add 4 g of poly(vinylidene fluoride-co-hexafluoropropylene) and 20 mL of N,N'-dimethylformamide, stir to dissolve, and then hot-press to obtain an electrolyte film.

[0031] Comparative Example 1: The difference between this comparative example and Example 1 is that the silicon-based composite material is replaced by a silicon-based material obtained by mixing elemental silicon and graphite in a mass ratio of 1:1 and ball milling.

[0032] Comparative Example 2: The difference between this comparative example and Example 1 is that the electrolyte film is replaced with an electrolyte prepared by mixing lithium hexafluorophosphate, ethylene carbonate, diethyl carbonate and fluoroethylene carbonate in a volume ratio of 1:1:1:0.3, the positive electrode is placed at the bottom of the battery, the electrolyte is added dropwise, and then the diaphragm is added, and finally the negative electrode is placed and sealed to obtain a lithium battery.

[0033] Comparative Example 3: This comparative example differs from Example 1 in that the composite silicon alloy is not subjected to pre-lithiation treatment, and the silicon-based composite material is prepared by carbonization.

[0034] Performance Testing The lithium batteries prepared in each embodiment and comparative example were charged and discharged at a constant current rate of 0.1C at 60°C. The first cycle discharge specific capacity, the first cycle charge specific capacity and the capacity retention rate after 50 cycles of charge and discharge were recorded. The first coulombic efficiency was calculated according to the following formula: ; FCE is the first coulombic efficiency; Q 放 The first cycle discharge capacity, unit is mAh / g; Q 冲 It is the first cycle charge capacity, in mAh / g.

[0035] The test results are shown in Table 1 below: Table 1 Lithium battery basic performance test results

[0036] The lithium batteries prepared in each embodiment and comparative example were charged and discharged at a constant current rate of 1C at 60°C, and the presence of short circuit was recorded after 600 hours of cycling. The lithium batteries prepared in each embodiment and comparative example were charged and discharged at 80°C for 120 minutes, and the presence of fire was recorded.

[0037] The lithium batteries prepared in each embodiment and comparative example were subjected to cyclic charge and discharge at 60° C., and the number of cycles when the battery capacity decayed to 60% was recorded.

[0038] The test results are shown in Table 2 below: Table 2 Test results of high temperature stability of lithium batteries

[0039] It can be seen from the data in the table that the lithium batteries prepared in Examples 1 to 3 have a first-cycle discharge specific capacity of 1436.3 to 1447.6 mAh / g, a first-cycle charge specific capacity of 1264.9 to 1297.5 mAh / g, an initial coulombic efficiency of 88.1 to 89.7%, and a capacity retention rate of 82.3 to 82.7% after 50 cycles of charge and discharge, indicating that the lithium batteries prepared in the present invention have excellent energy density and cycle life; the lithium batteries prepared in Examples 1 to 3 are charged and discharged at a constant current rate of 1C at 60°C, and there is no short circuit phenomenon after 600 hours of cycling, and there is no fire phenomenon after charging and discharging at 80°C for 120 minutes, indicating that the lithium batteries prepared in the present invention have excellent thermal stability.

[0040] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.

[0041] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the present invention to specific embodiments. Obviously, many modifications and variations are possible based on the contents of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the present invention, thereby enabling those skilled in the art to better understand and utilize the present invention. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a high energy density lithium-ion battery based on a silicon-based composite negative electrode, characterized in that: The steps include: S1. Preparing a positive electrode sheet: mixing lithium nickel cobalt manganese oxide, acetylene black, carbon nanotubes and polyvinylidene fluoride, adding the mixture to N,N'-dimethylformamide to prepare a positive electrode slurry, coating the mixture on a current collector, and drying the mixture to prepare a positive electrode sheet; S2. Prepare the negative electrode: mix the silicon-based composite material, polyvinylidene fluoride and acetylene black, add N,N'-dimethylformamide to prepare the negative electrode slurry, apply it on the current collector, and dry it to prepare the silicon-based composite negative electrode; S3. Assemble the battery: Assemble the negative electrode sheet, separator, electrolyte film and positive electrode sheet in an argon atmosphere in order from bottom to top to produce a high energy density lithium-ion battery based on a silicon-based composite negative electrode.

2. The method for preparing a high energy density lithium-ion battery based on a silicon-based composite negative electrode according to claim 1, characterized in that: In the negative electrode plate, the mass ratio of the silicon-based composite material, polyvinylidene fluoride and acetylene black is (75-80): (10-15): (15-20); In the positive electrode plate, the mass ratio of lithium nickel cobalt manganese oxide, acetylene black, carbon nanotubes and polyvinylidene fluoride is (94~96): (1.5~2): (0.2~0.3): (1.5~2); the separator is a polypropylene film.

3. The method for preparing a high energy density lithium-ion battery based on a silicon-based composite negative electrode according to claim 1, characterized in that: The method for preparing the silicon-based composite material comprises the following steps: S11, placing elemental silicon powder and metallic magnesium powder into a ball mill and milling them in an argon atmosphere, heating the mixture to react to obtain a magnesium-silicon alloy, etching the magnesium-silicon alloy in hydrochloric acid and hydrofluoric acid in sequence, washing, and drying the mixture to obtain porous silicon powder; S12, placing porous silicon powder, graphene, melamine and polyvinyl pyrrolidone in a ball mill and milling them to obtain a precursor, adding the precursor and ferric chloride to deionized water, adding dropwise an ethanol solution of fumaric acid, reacting at room temperature, washing with deionized water, drying and calcining to obtain a metal-organic framework-encapsulated silicon material, adding pyrrole and the metal-organic framework-encapsulated silicon material to deionized water for reaction to obtain a composite silicon alloy; S13. Add metallic lithium and biphenyl to tetrahydrofuran for reaction to obtain a pre-lithiation reagent, add the composite silicon alloy to the pre-lithiation reagent for pre-lithiation reaction, then add it to a phosphoric acid solution for reaction to remove lithium, wash with deionized water, dry, and then carbonize at high temperature, and grind to obtain a silicon-based composite material.

4. The method for preparing a high energy density lithium-ion battery based on a silicon-based composite negative electrode according to claim 3, characterized in that: The mass ratio of elemental silicon powder and metallic magnesium powder in the S11 is 1: (9~10), and the powder is ball-milled at a speed of 300~500 rpm in an argon atmosphere for 3~4 hours, heated to 600~700°C for reaction for 4~6 hours, etched in 5wt% hydrochloric acid for 4~6 hours, and then etched in 5wt% hydrofluoric acid for 4~6 hours.

5. The method for preparing a high energy density lithium-ion battery based on a silicon-based composite negative electrode according to claim 3, characterized in that: The mass ratio of porous silicon powder, graphene, melamine and polyvinyl pyrrolidone in the S12 is 3: (1~1.3): (0.4~0.5): (0.3~0.4), and the ball milling is carried out at a speed of 300~500rpm for 3~4h. The mass ratio of the precursor, ferric chloride and fumaric acid is 1: (2.6~3): (1~1.3). After adding an ethanol solution of fumaric acid dropwise, the mixture is reacted at room temperature for 20~24h, washed with deionized water and dried, and calcined at 700~800℃ for 4~6h. The mass ratio of the metal organic framework encapsulated silicon material and pyrrole is 10:1~2, and the mixture is added to deionized water and reacted at room temperature for 1~2h.

6. The method for preparing a high energy density lithium-ion battery based on a silicon-based composite negative electrode according to claim 3, characterized in that: The molar ratio of metallic lithium to biphenyl in S13 is (2-2.2):

1. The metallic lithium and biphenyl are added to tetrahydrofuran and reacted at room temperature for 10-12 hours. The composite silicon alloy is added to a pre-lithiation reagent and pre-lithiation is reacted at room temperature for 10-12 hours. The composite silicon alloy is then added to a 30-40 g / L phosphoric acid solution and reacted at room temperature for 4-6 hours. The composite silicon alloy is then carbonized at 800-850°C for 2-4 hours.

7. The method for preparing a high energy density lithium-ion battery based on a silicon-based composite negative electrode according to claim 1, characterized in that: The method for preparing the electrolyte film comprises the following steps: S21, adding ferric chloride, aluminum chloride and magnesium chloride to deionized water, adding sodium hydroxide and sodium bicarbonate dropwise to adjust the pH to 9.5-10, heating to crystallize, drying and grinding to obtain iron-doped hydrotalcite; S22. Mix lithium bis(trifluoromethanesulfonyl imide) and lithium dioxalatoborate, add 1-methyl-3-hexylimidazole fluoromethanesulfonyl imide ionic liquid, heat and stir, and vacuum dry to obtain a lithium-containing mixture, mix the lithium-containing mixture and iron-doped hydrotalcite, add poly(vinylidene fluoride-co-hexafluoropropylene) and N,N'-dimethylformamide, stir and dissolve, and then hot press to obtain an electrolyte film.

8. The method for preparing a high energy density lithium-ion battery based on a silicon-based composite negative electrode according to claim 7, characterized in that: The molar ratio of ferric chloride, aluminum chloride and magnesium chloride in the S21 is (0.1~0.2): (1.3~1.5): (5~6), the molar ratio of sodium hydroxide and sodium bicarbonate is 4:1, and the temperature is raised to 80~90°C for crystallization for 8~12 hours; the molar ratio of lithium bis(trifluoromethanesulfonyl imide), lithium bis(oxalatoborate) and 1-methyl-3-hexylimidazole-type fluoromethylsulfonyl imide ionic liquid in the S22 is (0.5~0.6): (0.3~0.4): 4.5, the temperature is raised to 50~60°C and stirred for 10~12 hours, and the mass ratio of the lithium-containing mixture, hydrotalcite and poly(vinylidene fluoride-co-hexafluoropropylene) is 1:1: (8~10).

Citation Information

Patent Citations

  • A long-cycle fast-charging SiO graphite composite anode material and its preparation method

    CN114628652B

  • A silicon-based composite anode material for all-solid-state lithium batteries and its preparation method

    CN117691096B

  • Manufacturing process of lithium ion solid-state battery

    CN117613362A

Cited By

  • Composite silicon-carbon negative electrode material and preparation method thereof, negative electrode plate and secondary battery

    CN121769109A